Visual digital culture : surface play and spectacle in new media genres - Darley, Andrew (Sussex studies in culture and communication., 2000)
Visual Digital Culture considers the effect of new image technologies on the forms and experience of mass visual culture. Examining the digital imaging techniques employed in films such as Forrest Gump and Toy Story, and across a wide range of media including music video, computer games, theme parks and simulation rides, Andrew Darley argues that contemporary visual culture is radically different from traditional visual culture--marking a break with the emphasis on story, representation, meaning and reading, favoring instead a focus on style, image performance and sensation.